The Impact of Job Stress on Job Satisfaction Among University Staff: Case Study at Jabatan Pembangunan, University Sains Malaysia (USM), Pulau Pinang - Mimi Hazwani, Abd Malek (2010)
This article investigates the relationship between job stress and job satisfaction. The determinants of job stress that have been examined under this study include, role conflict, workload pressure, homework interface, role ambiguity, and performance pressure. A convenience sample of 150 university staff from Universiti Sains Malaysia (USM), Pulau Pinang. The results show there is a significant relationship between four of the constructs tested. Pearson Product Moment Correlation to find out correlations and Multiple Linear Regression Technique were used to find out effect between variables. The finding indicates that factor such as external environment contribute to the occupational stress. This external factor is beyond the control of the organization. The occupational stress do not have direct effect on intention to leave and absenteeism but have direct negative effect on job satisfaction. Job satisfaction have negative effect on intention to leave and absenteeism.